Análise caracterização da dinâmica da Foz do Rio Apodi, região de Areia Branca/RN, com base na cartografia temática multitemporal de produtos de sensores remotos - Araújo, Armando Bezerra de (2006)
The study area islocated in the northern cost of Rio Grande do Norte State, preciselyin a west zone of Apodi-Mossoró River, inclunding Tibau City, Grossos City and part of Mossoró City. Geologicaly, this area is composed by rokcs of Potiguar basin, represented by Cretaceous, Tertiary and Quaternary sediments. This area is characterizer by the intense action of cosatal processes (eolic and costal tranports, generalized erosion, alteration in the sediments balance and coast modification), reponsable for it´s morfological instability, also the antropic interference, where the iol industry is located, next Mossoró City, and also the salt exploration industry and the tendency of expantion of shrimp cultivation. This report had as objective the multitemporalgeoenvorimentalmonitoring of the region by recognizingin the field and analizingimages of orbital sensors of diferents years of last four decades. This analisys was achieved by Digital Images Procesing (DIP) thecnics, com subsidized, in a GIS, the preparion of Thematic Maps of natural resources (Geology, Geomorphology and Use & Ocupatios of Earth) and the Envorimental Sensivity to Oil Spilling, main objective os this project. Such technics constitute important tools of envoriment monitoring and maneging, indicating tendencies of antropic of natural growing, making possible the apropiated planning of development of the region, where the steps can be indicated minimized possibles envorimental impacts caused by antropics interferencies on the region, mainly those related to industrial activities, and oil industry above all. Researchs of this nature are very important to the analisys and ordered manegements of use and ocupation of coastal places